How commercializing academic patents promote economic growth: mediating effect and spatial spillover - Jiafeng Gu (Applied Economics Letters, 2023)
Governmental investment in commercializing academic patents has spurred economic growth. This study explores the mechanism underlying the impact of academic patent commercialization on regional economic development based on holistic view of the integration of local and neighbourhood hierarchies. The empirical analysis of a sample of 31 Chinese provinces from 2010 to 2019 shows that fiscal expenditures on science and technology mediate the relationship between academic patent commercialization and economic development. Moreover, there is a positive spatial spill over effect between developing economies of neighbouring provinces. In the knowledge economy era, academic patent commercialization, supported by fiscal expenditure, plays an increasingly important role in regional economic growth.